Efektifitas Model Pembelajaran Mind Mapping Terhadap Keterampilan Menulis Narasi Siswa Kelas V Sekolah Dasar - Hafid, Abd; Jafar, Muh Idris; Fatmaisya, Dila (Universtas Negeri Makassar, 2025)
This study is a quantitative research of Quasi-experimental type which aims to determine the description of narrative writing skills of fifth grade students of SDN 10 Manurunge, Bone Regency and the effect of Mind Mapping learning model on narrative writing skills of fifth grade students of SDN 10 Manurunge, Bone Regency.. The sampling technique in this study used non-Probability Sampling in the form of saturated sampling. The data collection technique used was a written test by providing a pretest and posttest. The data analysis technique was descriptive and inferential analysis using Nonequivalent Control Group Design. Based on the results of descriptive statistical analysis, it showed an increase in students' narrative writing skills before and after the application of the mind mapping learning model, with an average pretest value of 60.36 and a posttest of 80.55. There was an increase of 33.44% after the application of the mind mapping learning model. Meanwhile, based on the results of the analysis of the Independent Sample t-Test, namely tcount (5.766) > ttable (1.67722). The conclusion of the study is that there is a significant influence of the application of the mind mapping learning model on the narrative writing skills of class V students at SDN 10 Manurunge.